Estudo sobre a formação da interface em soldas dissimilares de alumínio e aço galvanizado durante o processo de soldagem por fricção por ponto (RFSSW) com controle por carga - Ferrari, Vítor Ramos (Universidade Federal de São Carlos, 2022)
In the current scientific and technological scenario, the increased demand for dissimilar joints aiming a combination of optimized mechanical properties has driven innovations. Based on this, the present project proposes an in-depth study to elucidate the metallurgical aspects involved in the interface formation of dissimilar welds between aluminum alloy (AA6016-T6) and Zn-coated DX56D steel joined by refill friction stir spot welding (RFSSW) using load control. The main process parameters effects were evaluated through statistical methods and analysis. Subsequently, the metallurgical aspect was assessed through multi-scale microstructural characterization (optical and electron microscopy), mechanical tests (lap shear and microhardness) and thermal measurements (differential scanning calorimetry and thermal cycle). For the studied dissimilar joints, Zn incipient melting coupled with the presence of a low temperature eutetic reaction for an overall chemical composition Al – 88.7 %at. Zn led to semi-solid structure formation. The presence of liquid phases was essential for the process lubrication and interface protection from oxide contamination. When rapidly dispersed along the stir zone, the Zn-rich liquid phases also presented a directly influence on interfacial reaction, enabling the sheets joining through Al5F2(Si) intermetallic compounds formation. Therefore, the complex relationship between microstructure and mechanical properties were discussed in terms of material flow and Zn-induced intermetallic compounds growth acceleration. The bake hardening presented a substantial influence on diffusional precipitation mechanisms, maximizing the joints ultimate lap shear strength while limiting the sheets secondary bending. Overall, the results highlight a great potential of load-controlled RFSSW method for producing high-strength dissimilar joints through short thermal cycles, which is favorable for applications in automotive industries.
Study on interface formation in dissimilar aluminum to galvanized steel welds during refill friction stir spot welding using load control
Keywords: Soldagem por fricção por ponto; AA6016-T4; Aço galvanizado DX56D; Composto intermetálico; Fusão incipiente; Fluxo de zinco; Refill friction stir spot welding; Galvanized DX56D steel; Intermetallic compound; Incipient melting; Zinc flow; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA DE TRANSFORMACAO; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA